A STUDY ON FACTORS INFLUENCING CREDIT RISK MANAGEMENT IN INDIAN FINANCIAL INSTITUTIONS (CAHIERS MAGELLANES-NS, 2024)
Indian Financial Institutions face a significant challenge with Credit Risk, as it is difficult to recover lent funds from borrowers. To understand the factors that impact Credit Risk Management in these institutions, a study was conducted using data collected from 26 institutions, including 6 non-banking and 20 banking institutions, from 2012 to 2021. The study considered both individual and macro-economic determinants as variables, with Gross Non-Performing Assets (GNPA) as the dependent variable, and several factors including Capital Adequacy Ratio (CAR), Return on Capital Employed (ROCE), Asset Quality, Return on Assets (ROA), Market Capitalization (MCAP), bank size, Gross Domestic Product (GDP), inflation, Consumer Price Index (CPI), unemployment rate, and real interest rate as the independent variables. A Hausman test was conducted to identify the best-fit model for the panel data regressions. The results of the study suggest that ROA, MCAP, GDP, and Unemployment Rate are the primary factors that impact Credit Risk Management in Indian Financial Institutions. It is recommended that institutions focus on maintaining a healthy ROA and MCAP, while also monitoring macroeconomic factors such as GDP and the unemployment rate to mitigate credit risk. The study further indicates that Credit Risk Management should consider a combination of individual and macroeconomic determinants, rather than relying solely on individual factors such as CAR, ROCE, and asset quality. In conclusion, this study provides valuable insights for financial institutions to develop effective Credit Risk Management strategies. By considering the identified determinants of Credit Risk, institutions can mitigate their losses and maintain a stable financial position.